Analysis of Potential Ecotourism in the Rawa Bento, Kerinci District - Cory Wulan; Albayudi Albayudi; Tiara Lidiarti (Fakultas Kehutanan Universitas Jambi, 2019)
Ecotourism is a trip to an area both natural and artificial and existing culture that is informative and aims to ensure the preservation of nature and socio-culture. Rawa Bento is one of the nature tourism areas and has a unique, rare and beautiful view. Rawa Bento has a lot of potential object that has not been utilized optimally, therefore this study aims to determine the potential of Rawa Bento using the ADO-ODTWA guidelines. The method of data retrieval is done through field observations, questionnaire interviews, literature studies, and documentation. The results showed that the assessment of ecotourism in Rawa Bento area of Kerinci Regency had very potential results in the criteria of accessibility, accommodation, facilities and infrastructure as well as availability of fresh water, while attractiveness and environmental conditions only received potential value. Keywords: Culture, ecotourism, Kerinci district, Rawa Bento